(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
This study aimed to analyze the role of private kindergarten directors in Latakia in enabling children to cope with disasters through activities, initiatives, and communication with parents and the local community. A descriptive-analytical approach was adopted, and a comprehensive questionnaire was prepared covering three dimensions: initiatives and activities, communication with parents, and communication with the local community. The questionnaire was distributed to a sample of 76 directors, and the data were analyzed using averages and percentages. The findings revealed that the role of the directors was moderate across all dimensions, with an overall relative weight of 59%. Communication with parents achieved the highest average, followed by initiatives and activities, and finally, communication with the local community. The results also indicated no statistically significant differences attributed to the variables of academic qualifications or years of experience. The moderate performance level was attributed to a lack of resources and institutional support, alongside the absence of targeted training programs. Based on these findings, the study recommends developing specialized training programs for directors to better prepare children for coping with disasters. Additionally, the study suggests creating an illustrated guide for children that includes appropriate safety procedures for various disasters and fostering collaboration between kindergartens and specialized organizations, such as civil defense. The importance of this study lies in addressing a critical issue within a local context while offering practical recommendations to enhance educational and administrative performance in kindergartens.